PENGARUH PERSEPSI RISIKO, KEPERCAYAAN DAN KUALITAS INFORMASI TERHADAP PROSES KEPUTUSAN PEMBELIAN SECARA ONLINE (Studi pada Konsumen di Ungaran Kabupaten Semarang) - Adnan Surya Azhari, 13.05.51.0223; Tjahjaningsih, Endang (Students Journal of Economic and Management, 2017)
The study of a very important purchasing decisions made by businessmen who market their products online. The purpose of the study was to analyze the influence of perception of risk, trust, information quality on purchasing decisions online. A sample of 100 respondents, using a non-probability sampling technique with the sampling method used is purposive sampling, its sampling with the criteria that the respondent is an adult and has been making purchases online. Methods of research data analysis using linear regression. The test results showed that there are negative and significant effect between the perception of risk on purchasing decisions online. there are significant positive and significant correlation between trust in purchasing decisions online, there is a positive and significant influence between information quality on purchase decisions online Â Keywords: risk perception,Â  trust, information quality and purchasing decisions onlineDAFTAR PUSTAKAAkbar M.M. dan N. Parvez, (2009). Impact of Service Quality, Trust, and Customer Satisfaction on Customer Loyalty. ABAC Journal Vol. 29, No 1 (January-April 2009, pp.24-38).Alhasanah, Kerthadi, Riyadi. 2014. Pegaruh kegunaan, Kualitas Informasi dan Kualitas Interaksi Layanan Web E-commers terhadap Keputusan Pembelian Online (Survei Pada Konsumen www.Getscoop.com). Jurnal Administrasi Bisnis (JAB) Vol. 15 No. 2 Oktober 2014.Ardyanto, Denny; Susilo, Heru dan Riyadi, 2015. Pengaruh Kemudahan an Kepercayaan menggunakan E-Commerce terhadap Keputusan Pembelian Online (Survei Pada Konsumen www.petersaysdenim.com). Jurnal Administrasi Bisnis (JAB) Vol. 22 No. 1 Mei 2015.Basu Swastha. 2000. Pengantar Bisnis Modern, Pengantar Ekonomi Perusahaan Modern. Jakarta : Liberty.Chaffey, Dave; et al. 2007. Internet Marketing. Pearson Education limited., England.Djarwanto, PS dan Subagyo, Pangestu. 2000. Statistik Induktif. Edisi Ke-empat. Yogakarta: BPFE.Elissa, Ingge dan Mujiyana. 2013. Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Via Internet pada Toko Online. Jurnal Ekonomi Manajemen Universitas DiponegoroEngel, James F, et.al., 1995, Consumen Behavior, Alih Bahasa: Budiyanto, Jilid 1 dan 2, Bina Rupa Aksara, Jakarta.Fandy Tjiptono, 2008. Service Manajemen. Yogyakarta : Andi OffsetGefen, D., Karahanna, E., and Straub, D. W. 2004. "Trust and TAM in Online Shopping: An Integrated Model." MIS Quarterly, 27(1), 51-90.Ghozali, Imam, 2011, Aplikasi Analisis Multivariate Dengan Program IBM SPSS 19 (Edisi Kelima), Semarang: Universitas Diponegoro.Hiam, Alexander & Charles D. Scewe. 1994. The Portable MBA Pemasaran.Â  Jakarta : Binarupa AksaraKharisma Rizki H, Endang S, Heru Susilo 2015, Kemudahan, Kualitas Informasi terhadap Minat dan Keputusan Pembelian Secara Online, Jurnal Administrasi Bisnis, Vol. 28 No. 1Kotler, Philip, and Gary Armstrong, 2004. Principles of Marketing, Prentice Hall Inc., Englewood Cliffs, New JerseyMorgan, R.M., & Hunt. S.D., 1994, The Commitment-Trust of The Relationship Marketing, Journal of Marketing, July, Vol. 58, No.3, pp.20-38Oglethorpe, J. E and Monroe, B. K., 1994, Determinant of Perceived Health an Safety Risk of Selected Hazardous Product and Activities, Journal of Consumer Research, No.28Park, C.H., & Kim, Y. G. (2003). Identifying Key Factors Affecting Consumer Purchase Behavior In An Online Shopping Context. International Journal of Retail & Distribution Management, Vol.31, No.1, pp.16-29.Soliha, N. F. (2017). Kualitas Produk, Citra Merek dan Presepsi Harga Terhadap Proses Keputusan Pembelian Konsumen Sepeda Motor Matic âHondaâ. Jurnal Manajemen Teori dan Terapan , Tahun 10. No. 1.Sugiyono. 2010. Metode Penelitian Administrasi.Bandung : CV AlfabetaSuhir, Moch; Suyadi, Imam; dan Riyadi, 2014. Pengaruh Persepsi risiko, Kemudahan dan Manfaat terhadap Keputusan Pembelian Secara Online (Survei Terhadap Pengguna Situs Website www.Kaskus.co.id). Jurnal Administrasi Bisnis JAB Vol. 8 No. 1 Februari 2014Schiffman, Leon G. And Leslie L. Kanuk. 2007. Consumer Behavior. Fifth Edition, Prentice-Hall Inc. New JerseySukma, Abdurrahman Adi., 2012, Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Social Networking Websites, Jurnal Ekonomi Manajemen, Fakultas Ekonomi Universitas GunadarmaSuresh, A.M dan Shashikala R. 2011. âIdentifying Factors of Consumer Perceived Risk towards Online Shopping in Indiaâ. International Conference on Information and Financial Engineering IPEDR. Vol 12 hal 346-341Ujang Suwarman, 2002, Perilaku Konsumen Teori dan Penerapannya dalam Pemasaran, Penerbit: PT Ghalia Indonesia, Bogor.Venny Rizky, Amelia Aziz,Â  2015. Pengaruh Presepsi Risiko dan Gaya Hidup Terhadap Keputusan Pembelian Pakaian Secara Online melalui Blackberry Massanger (BBM). Ejournal piskologis 2015, 4(1);95-106Wolfinbarger, M.F. and Gilly, M.C. (2003). Etailq: Dimensionalizing, Measuring And Predicting Etail Quality. Journal of Retailing, Vol. 79 No. 3, pp. 183-98.Â www.apjii.comwww.wikipedia.comYusnidar, Samsir, dan Restuti, Sri, 2014. Pengaruh Kepercayaan Dan Persepsi Resiko terhadap Minat Beli dan Keputusan Pembelian Produk Fashion Secara Online di Kota Pekanbaru. Jurnal Sosial Ekonomi Pembangunan Tahun IV No. 12 Juli 2014Â